Removal of Cu (ll) From Aqueous Solution Using Polyacrylic Acid Hydrogel Beads as Adsorbent - Al-Abachi, Mouayad; Al- Awady, Nagam; Al-Anbakey, Ahmed (Iraqi Journal of Science, 2024)
In this article, the adsorption of Cu(ll) ion from aqueous solution into polyacrylic acid(PAA) hydrogel bead has been investigated using a batch method of differenttemperature (10-30 °C) and different contact time (1-48 hr) to reach the equilibrium ofadsorption. Initial concentration and adsorption capacity of the adsorbents is presented,the time required to reach a maximum capacity of bead was about 24hr. The temperatureeffect on adsorption was studied and the experimental data have been analyzed using theLangmuir and freundlich isotherm models. The adEsorption capacity at equilibrium wasfound to be 142.68 mg/g; more than 95% of studied cation was removed by theadsorbent. The process is very efficient especially at low concentration of pollutants inaqueous solutions.